(untitled) (In situ, 2024)
Pećina (cave) in Ždrilo near Rovanjska has long been known in the literature as an Early Neolithic site. During recent years, trial and systematic excavations have confirmed the existence of an important Neolithic stratigraphic sequence primarily related to the deposition of the so-called "layer-cake" facies of the layers that suggest the function of the structure as a place for animal stabling. The Palaeolithic phase, despite few small archaeological finds, indicates the use of the cave in the Upper and possibly Middle Palaeolithic.